The Influence of TikTok Marketing Content and Facetology Brand Image on Purchase Decisions Mediated by Purchase Intention - Hadi, Dhea Savira; Sumarwan, Ujang; Nurhayati, Popong (International Journal Labs, 2025)
This study aims to analyze the influence of TikTok marketing content and brand image on purchasing decisions mediated by purchase intention. This study is based on the increasing role of social media, particularly TikTok, as an effective marketing channel for beauty brands in reaching the younger generation (Gen Z). Facetology, as a local beauty brand, actively provides interactive content on TikTok with the hope of building a positive brand image and encouraging purchases. This study uses quantitative research, with data obtained through an online questionnaire distributed to 132 respondents who are followers of Facetology on TikTok and have viewed its marketing content. This study employs Structural Equation Model-Partial Least Square (SEM-PLS) data analysis techniques and descriptive analysis to explain the obtained data. The study includes four variables: marketing content, brand image, purchase interest, and purchase decision. The research period was conducted from June to July 2025. The results of this study indicate that marketing content has a positive and significant influence on purchase intention. Furthermore, brand image also has a positive and significant influence on purchase intention. Purchase intention, as the mediating variable, also has a positive and significant influence on purchase decision